Autophagy Regulates VDAC3 Ubiquitination by FBXW7 to Promote Erastin-Induced Ferroptosis in Acute Lymphoblastic Leukemia - Zhu, Ting; Liu, Bo; Wu, Di; Xu, Gang; Fan, Yang (Frontiers in Cell and Developmental Biology, 2021)
Background: The discovery of ferroptosis is a major breakthrough in the development of cancer treatments. However, the mechanism by which ferroptosis contributes to acute lymphoblastic leukemia (ALL) is to be clarified. Here, we explored erastin-induced ferroptosis in ALL cells and the impact of autophagic activity on this process. Materials and Methods: Cell viability was evaluated in various ALL cell lines following erastin treatment by the MTS assay, while cell death was evaluated via a trypan blue assay. Immunoblotting and quantitative real-time PCR were used to detect protein and mRNA expression, respectively. The UbiBrowser database was used to predict the E3 ligase of VDAC3, which was confirmed by immunoprecipitation. The role of FBXW7 in erastin-induced ferroptosis in vitro was evaluated via lentiviral-mediated silencing and overexpression. ALL xenograft mice were used to observe the impact of autophagy on erastin-induced ferroptosis. Results: Resistance to erastin-induced ferroptosis was higher in Jurkat and CCRF-CEM cells than in Reh cells. The sensitivity could be modified by the autophagy activator rapamycin (Rapa) and the autophagy inhibitor chloroquine (CQ). Rapa sensitized ALL cells to erastin-induced ferroptosis. In ALL xenograft mice, the combination treatment of Rapa and erastin resulted in longer survival time than those observed with erastin or Rapa treatment alone. VDAC3 was regulated by autophagy post-transcriptionally, mainly via the ubiquitin-proteasome system (UPS). FBXW7 was verified as a specific E3 ligase of VDAC3. FBXW7 knockdown attenuated VDAC3 degradation by suppressing its ubiquitination, thereby increasing the sensitivity of ALL cells to erastin. Conclusion: Autophagy regulated erastin-induced ferroptosis via the FBXW7-VDAC3 axis. Rapa sensitized ALL cells to erastin-induced ferroptosis both in vitro and in vivo. Our findings provide potential therapeutic targets for ALL.